2003
DOI: 10.1161/01.res.0000089257.94002.96
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Independent Activation of Vascular Endothelial Growth Factor Receptor 2 by Fluid Shear Stress Regulates Activation of Endothelial Nitric Oxide Synthase

Abstract: Abstract-Fluid shear stress generated by blood flowing over the endothelium is a major determinant of arterial tone, vascular remodeling, and atherogenesis. Nitric oxide (NO) produced by endothelial NO synthase (eNOS) plays an essential role in regulation of vascular function and structure by blood flow, but the molecular mechanisms that transduce mechanical force to eNOS activation are not well understood. In this study, we found that laminar flow (shear stressϭ12 dyne/cm 2 ) rapidly activates vascular endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
305
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(319 citation statements)
references
References 52 publications
13
305
0
1
Order By: Relevance
“…Considerable data suggest that increased force/shear stress on PECAM‐1 leads to Src kinase activation (Chiu et al , 2008) and phosphorylation and ligand independent activation of VEGFR2 and VEGFR3. Activated VEGFR2 and VEGFR3 can trigger several pathways that lead to the activation of integrins and subsequent downstream signalling, including the release of vasoactive signals and vessel dilation (Jin et al , 2003; Fleming et al , 2005). Shear detection requires cell anchorage to the underlying ECM, the nature of which appears to influence the response of the endothelium, since endothelial cells bound to fibronectin versus collagen type I lead to stronger adhesion, manifested as larger and more complex focal adhesions and stronger tension development on PECAM‐1 (Collins et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Considerable data suggest that increased force/shear stress on PECAM‐1 leads to Src kinase activation (Chiu et al , 2008) and phosphorylation and ligand independent activation of VEGFR2 and VEGFR3. Activated VEGFR2 and VEGFR3 can trigger several pathways that lead to the activation of integrins and subsequent downstream signalling, including the release of vasoactive signals and vessel dilation (Jin et al , 2003; Fleming et al , 2005). Shear detection requires cell anchorage to the underlying ECM, the nature of which appears to influence the response of the endothelium, since endothelial cells bound to fibronectin versus collagen type I lead to stronger adhesion, manifested as larger and more complex focal adhesions and stronger tension development on PECAM‐1 (Collins et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it was shown that shear stress activated VEGFR2 via conformational change in a ligand-independent manner [24]. The present work indicates that stretch may activate VEGFR2 through similar mechanism based on the following lines of evidence: (1) the VEGF-neutralizing antibody did not affect stretch-induced VEGFR2 phosphorylation ( Figure 3C); (2) the VEGF-neutralizing antibody failed to block stretch-induced WPB exocytosis and leukocyte adhesion in cultured ECs ( Figure 3E Figure S3); (3) mechanical stretch activated VEGFR2 that was exogenously expressed in 293A cells and its downstream signaling pathways (Supplementary information, Figure S4), similar to the case of the activation of angiotensin II type 1 receptor by stretch [25].…”
Section: Discussionmentioning
confidence: 99%
“…In general, PI3-kinase is activated by translocation to the plasma membrane after phosphorylation of transmembrane tyrosine kinase receptors and subsequent interaction of PI3-kinase SH2 domains with phosphotyrosine residues in the receptors (51). It has recently been shown that flow activates PI3-kinase by inducing Src kinase activation and subsequent ligand-independent activation of tyrosine kinase receptors such as the VEGF and purinergic P 2 receptors (26,45). Given that c-Src is expressed in the THAL (28), it is tempting to speculate that flow-dependent activation of c-Src mediates PI3-kinase activation and eNOS trafficking in the THAL.…”
Section: Discussionmentioning
confidence: 99%